The relationship between anxiety levels and psychological resilience of earthquake victims and their cigarette and internet use - Dinçer, Burcu; Demirkol, Mehmet Emin; Tamam, Lut; Yeşiloğlu, Caner (Journal of Dependence, 2025)
Objective: This study aimed to evaluate the relationship between anxiety levels, psychological resilience, and addictive behaviors among individuals who experienced the February 6 earthquake in Osmaniye. Method: The sample consisted of 384 individuals affected by the earthquake. Participants completed the Beck Anxiety Inventory, Brief Resilience Scale, Fagerström Test for Nicotine Dependence, and Young’s Internet Addiction Scale. Results: Of the 384 participants, 65.4% were female, and 36.5% were aged 25–34. Women exhibited higher anxiety levels, while men showed greater psychological resilience and tobacco use. No gender difference was found in internet addiction. High school graduates had higher tobacco dependence, and low-income individuals displayed greater internet addiction. A significant relationship was identified between tobacco and internet addiction, with anxiety levels predicting both. Higher psychological resilience was associated with lower addictive behaviors. Conclusion: Individuals with higher psychological resilience exhibited lower rates of tobacco and internet addiction, while those with elevated anxiety showed higher prevalence of these addictions. Psychological resilience may serve as a protective factor against addictive behaviors.